Sharia Financial Institutions Compliance Towards Islamic Principles in Performing Intermediation Functions - Usman, Mizaj Iskandar (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2022)
This study aims to determine the factors of non-compliance with Islamic principles in Islamic Financial Institutions (IFIs). This article argues that IFIs must comply with Islamic principles based on the DSN-MUI fatwa, even though in the Indonesian legal hierarchy, DSN-MUI fatwas are not binding. IFIs show ambiguity in complying with Islamic principles when carrying out their intermediation function. Several other factors also cause IFIs' lack of compliance with sharia principles. These include the lack of applicability of the DSN-MUI fatwas, the conflict of interest of the Sharia Supervisory Board (SSBs), and competency issues among SSBs members. To address these issues, it is necessary to strengthen the regulations that make DSN-MUI an authoritative institution in establishing the sharia principles and the fatwas methodology. Thus, the fatwas are more applicable and avoid ambiguity. Furthermore, SSBs need re-structurization to be independent internal supervisory agencies. AbstrakPenelitian bertujuan mengetahui faktor-faktor ketidakpatuhan lembaga keuangan syariah (LKS) pada prinsip-prinsip Islam. Artikel ini menyebutkan LKS harus mematuhi prinsip-prinsip Islam sesuai fatwa DSN-MUI, walaupun dalam hierarki hukum Indonesia, DSN-MUI bukanlah sebuah lembaga otoritatif yang menerbitkan hukum mengikat. LKS tampak ambigu dalam mematuhi prinsip-prinsip Islam saat menjalankan fungsi intermediasinya. Ketidakpatuhan LKS kepada prinsip-prinsip syariah juga disebabkan oleh beberapa faktor lain, seperti: tidak aplikatifnya fatwa DSN-MUI; munculnya konflik kepentingan DPS; dan masalah kompetensi anggota DPS. Untuk mengatasi masalah-masalah tersebut, perlu adanya perbaikan regulasi yang menjadikan DSN-MUI sebagai lembaga otoritatif, agar fatwa yang dikeluarkan lebih aplikatif dan tidak menimbulkan multi tafsir. Sementara dari sisi DPS, perlu adanya regulasi merestrukturisasi organisasi DPS dengan menepatkannya sebagai lembaga pengawas internal yang independen.